Gender Justice and Islamic Family Law Reform in Malaysia - Zanariah Noor (Kajian Malaysia, 2007)
The study discusses the changing perceptions toward gender justice in socio-legal context of Malay society. The transmission of Egyptian reformists’ ideas regarding gender justice to Malay society through the Azharites, increasing education provided to women as well as the interaction between Malay intellectuals with Western civilization are among the factors which had contributed to these changes. To conform with the modern nation-state, the fiqh rules have been selectively codified and gradually drafted onto unified legal systems, inspired by a Western model. The transformation of fiqh rules to statutory law in the realm of family law were justified on the principale of judicious policy which enabled the rules to be changed, so as to conform with the changing modern Muslim society.